Mediator margins in the dairy supply chain and factors influencing marketing preferences in Eastern Mediterranean region of Turkey - Can, Mehmet Ferit; Gunlu, Aytekin; Aral, Yilmaz; Sahin, Tugba Sarihan; Arikan, Mehmet Saltuk (Tubitak Scientific & Technological Research Council Turkey, 2021)
The purpose of this study is to identify the shares of the intermediaries in the Eastern Mediterranean region milk supply chain (I) and to estimate the factors influencing the raw milk marketing preferences of milk producers (II). The research was conducted in 2017 with 102 dairy farms and 36 dairy industry enterprises in Hatay, Kahramanmaras, and Osmaniye provinces. As a result of the research, it was found that 85% of the milk produced by dairy farms was offered to the market, 65% of the milk entering the supply chain was transferred to the dairy industry and the average capacity utilization rate of the industry was 37%. It was found that the most rational chain for the milk producers and dairies among the 4 main marketing channels in the region is the third channel, which has two stages. Binary logistic regression was found to be significant (p < 0.01) as a whole. It was found that scale and price variables explained the variation in marketing preference by 70%. The cattle unit in the livestock enterprise has a positive effect on the transfer of milk to the industry, and the possibility of selling the milk directly at a higher price has a negative effect. For a more sustainable market organization and supply chain, business scales need to be increased and raw milk prices should be linked with production costs.
Keywords: Dairy; marketing; milk supply chain; price; producer